Determining the competency of children with developmental delays to testify in criminal trials - Van Niekerk, Hester Aletta (Rhodes University, Faculty of Law, Law, 2015)
In South Africa children are required to testify under oath or admonition. The shortcomings of the competency test are of particular relevance to children with developmental disabilities, since courts are not equipped to adequately assess the competency of these children to give evidence. One component of testimonial competency, namely the understanding of the concepts truth and lies, is overemphasised and is examined with questions that are developmentally inappropriate for child witnesses in general. For children with cognitive disabilities, such questions create barriers for participation in the truth-seeking process. Consequently, convictions have been set aside on appeal owing to procedural irregularities found in the implementation of this test. In the literature review on testimonial competency, attention was given to restrictions that specific developmental disabilities impose on the perceptual, cognitive, communication and moral development of children. Two of four components "“ narrative ability and moral capacity "“ were studied in a sample of 184 children in middle childhood. Participants' ability to give coherent and detailed accounts of events, their understanding of the concepts truth, lies, promises and the oath, and the Lyon and Saywitz oath-taking competency test, were investigated. Quantitative and qualitative methods were used for data analysis. Three groups were identified: those children with very limited, average or full testimonial competency. Their capacities were found to be related to maturation of cognitive functions and level of intellectual functioning. Participants were better able to demonstrate their understanding of truth and falsity by responding to the oathtaking test than giving verbal descriptions of these concepts. Whereas 1 percent of participants had a conceptual understanding of an oath, 15 percent understood the concept of a promise. Syncretism and confabulation compromised the narrative accounts of a substantial number of participants. Syncretism relates to immature narrative ability: correct details are combined in an illogical fashion. Confabulation refers to filling memory gaps with fabricated information. Guidelines on the competency determination of children with developmental disabilities were compiled. It is suggested that the competency examination be replaced by a formal, pre-trial competency assessment. The court should also receive expert evidence on how to facilitate meaningful participation when a child with sufficient testimonial competence is the witness.
Keywords: Child witnesses -- South Africa; Developmentally disabled children -- South Africa; Children -- Legal status, laws, etc. -- South Africa; Evidence (Law) -- South Africa